Active Vibration Control Of The Suspended Handle Using Inertia-Type Piezoelectric Actuator - Tan, Sak Jie (Universiti Sains Malaysia, 2019)
This study presents the active vibration control (AVC) using inertia-type piezoelectric actuator to attenuate the vibration of the suspended handle experimentally. Firstly, the Experimental Modal Analysis (EMA) of the suspended handle is conducted and the results shows that, the handle has four natural frequencies and mode shapes within 100 Hz to 500 Hz which in x axis at 520 Hz and 1558 Hz, y axis at 90 Hz and 186 Hz and z-axis at 454 Hz. Then, the characteristics of the inertia piezoelectric actuator are investigated where the works are separated into force and acceleration investigation. The maximum force generated by the inertia piezo actuator is 0.68N at frequency of 500 Hz with 4V of voltage when 95g of mass is applied to the actuator and the maximum acceleration of the inertia piezo actuator is 0.01 ms−2 at 500Hz with 4 V of voltage when 45g of mass is applied to the actuator. Finally, the inertia piezoelectric actuator is applied to the AVC system to overcome the vibration of the suspended handle using frequency independent and dependent excitation. For the frequency independent, the result shows that, the active suspended handle can reduce the acceleration level up to 39.69% at 400Hz of frequency for the 45g of inertia mass. Meanwhile, for the frequency dependent, the active suspended handle can reduce the acceleration level at the natural frequency of the handle up to 34.98%. The results of the study proved that, this active suspended handle is possible to be applied to the power tools for the vibration reduction.